"Dose-Response" Vulnerability Assessment of Urban Power Supply Network: Foundation for Its Sustainability and Resilience. (20th December 2018) - Tang, Haizhou; Zhao, Xudong; Chen, Zhilong; Xu, Jiheng; Su, Xiaochao
Abstract : Urban power supply network plays a vital role in maintaining the city operation. The vulnerability of power supply network in the face of events has been one of significant concerns. This study presents a new methodology and framework for "dose-response" vulnerability assessment of urban power supply network. This framework can explore the vulnerability of power supply network under two types of events: random type and intentional type. It also integrates a new metric that calculates the vulnerability of power supply network in both structural dimension and functional dimension. Taking the power supply network of a city in east China as an example, network vulnerability under different types of events was assessed, and the "dose-response" interrelationships between network performance and event scale under different types of events were thoroughly discussed. The results demonstrated that power supply network was more vulnerable to intentional events in both dimensions. For intentional events, power supply network was more vulnerable to degree-based attack than to betweenness-based attack. After that, the redundancy coefficient α of power supply network was optimized. The conclusion and some suggestions for future research were given in the end.